Templated diamond growth on porous carbon foam decorated with polyvinyl alcohol-nanodiamond composite. (August 2017) - Varga, M.; Stehlik, S.; Kaman, O.; Izak, T.; Domonkos, M.; Lee, D.S.; Kromka, A.
Abstract: Porous and self-standing structures are highly promising as membranes, electrodes, high sensitivity gas sensors, and supercapacitors due to their high surface area and tuneable surface properties. Composition of such materials with a polycrystalline diamond film may provide new functionalities for biological and electrochemical applications. However, the diamond growth on foreign substrates as a pinhole-free continuous thin film is still a not a trivial task. Here, we present a successful templated deposition process of polycrystalline diamond film on reticulated vitreous carbon foam (C-foam). Samples of polyvinyl alcohol (PVA) polymer-nanodiamond (ND) mixtures with various ND concentrations were prepared and characterized by means of optical spectroscopy, Raman spectroscopy, dynamic light scattering, zeta potential and pH measurements. The ND/PVA mixtures are employed for the preparation of diamond film by microwave plasma enhanced chemical vapour deposition process, and the effect of their composition (NDs/PVA ratio) on the nucleation (seed density, clustering) and diamond growth (substrate etching, polymer transformation) is analysed. The nucleation, early-stage of diamond growth and the resulting diamond-coated C-foams are characterized by scanning electron microscopy, atomic force microscopy and Raman spectroscopy. The obtained results underline the importance to tailor the NDs/PVA ratio for a well-defined three-dimensional C-foam coverage with the continuous diamond film. Graphical abstract: